"Poezja okolicznościowa w Polsce w latach 1730-1830" – zwycięska publikacja Wydawnictwa Uniwersytetu Rzeszowskiego - Magryś, Roman (Wydawnictwo Uniwersytetu Rzeszowskiego, 2014)
The article presents a longer news note on awarding the Rzeszow University Publishing House the Grand Prize of the Rector of Adam Mickiewicz University in Poznań for the best university book during the 18th Poznań (not just Science) Book Days, which took place in November 2014. The Publishing House received it for a monograph in the history of literature specified in its title. The note presents the most important stages of editorial and publishing work on the awarded book and briefly describes its scholarly value.
"The Occasional Poetry in Poland, in the years 1730-1830" – a Victorious Publication by the Publishing House of Rzeszow University
Keywords: książka akademicka; konferencja; monografia; nagroda; oświecenie; poezja okolicznościowa; Poznań; redaktor; rektor; targi; Uniwersytet Rzeszowski; wydawnictwo; scholarly book; conference; monograph; prize; Enlightenment; occasional poetry; editor; rector; book fair; Rzeszów University; publishing house